Dva poskusa pojmovanja stilistike - Uhlik, Mladen (Slavistična revija, 2014)
During the first two decades of the twentieth century, Charles Bally (1865-1947) and Grigorij Vinokur (1886-1947) made an attempt, each in his own way, at establishing stylistics as new applied linguistics. Nonetheless, as will be shown in the present paper, the object of stylistics of the two linguists differed. This paper will focus on the problems, raised by the two different approaches, as well as on the description of the different contexts, in which these two conceptions were formulated. In conclusion, it will be examined to what extent the differences are linked to two different linguistic schools of thought which are based on different philosophical assumptions.
Keywords: Bally, Charles, 1865-1947; colloquial language; govorjeni jezik; history of linguistics; jezikovne funkcije; knjižni jezik; language functions; speech langauge; standard language; stilistika; stylistics; theory of literary language; Vinokur, Grigorij, 1886-1947; zgodovina jezikoslovja